Student Characteristics and Behaviours in Childhood Predict Self‐reported Health in Middle Adulthood. Issue 5 (September 2016) - Spengler, Marion; Roberts, Brent W.; Lüdtke, Oliver; Martin, Romain; Brunner, Martin
Abstract: We examined how self‐reported and teacher‐rated student characteristics in primary school were associated with adult self‐reported health. A representative sample of Luxembourgish students was assessed in 1968 ( M age = 11.9, SD = 0.6) and 2008 (N = 745; M age = 51.8, SD = 0.6). Self‐reported sense of inferiority and pessimism in childhood were negatively related to subjective health and vitality‐related quality of life/health in adulthood (rs = −.08 to −.12); teacher‐rated studiousness (age 12 years) was positively related to subjective health, healthcare utilization and vitality‐related quality of life/health (age 52 years; rs = .13 to .16). After controlling for childhood IQ, parental socio‐economic status, educational attainment and sex in multiple regression analyses, most effects of teacher‐rated studiousness showed incremental validity beyond the controls. School entitlement, sense of inferiority, impatience and pessimism were positively related to body mass index (rs = .08 to .13). The responsible student scale and teacher‐rated studiousness were negatively related to body mass index (rs = −.09 to −.13). The findings demonstrate that childhood characteristics and behaviours are important life‐course predictors of key health dimensions beyond childhood IQ and parental socio‐economic status. In addition, this narrower level of assessment adds significantly to the empirical body of knowledge on long‐term predictors of health outcomes in adulthood. Copyright © 2016 European Association of Personality Psychology.